Above‐ground plant metabolomic responses to plant–soil feedbacks and herbivory. (25th April 2020) - Huberty, Martine; Choi, Young Hae; Heinen, Robin; Bezemer, T. Martijn
Abstract: Understanding the causes of variation in foliar plant metabolomes is essential for our understanding of ecological interactions between plants and other organisms. It is well‐accepted that foliar herbivory alters metabolites in leaves. However, soil (micro)organisms can also induce such changes. We generated plant‐specific soil legacies by growing 12 plant species individually in a common starting soil. Then we planted all plant species in all soils and exposed a subset to foliar herbivory. We then used 1 H nuclear magnetic resonance to analyse the shoot metabolomes of all responding plants. Above‐ground herbivory and soil legacies altered shoot metabolomes. In most plant species, soil legacy more strongly affected shoot metabolomes than foliar herbivory. Synthesis . Our results show that plant‐induced changes in soil alter metabolomes of plants that grow later in those soils. Such below‐ground legacy effects can have far‐stretching consequences for above‐ground multitrophic interactions as these often depend on the plant chemical composition. Recently, plant–soil feedbacks have received considerable attention in ecological studies, and our study now highlights that these feedbacks can be an important determinant of the often unexplained intraspecific variation in chemical composition among plants. Abstract : We show that plant‐specific soil legacies can impact the leaf metabolome of most of the 12 tested plant species. The effect of soil legacies on the metabolome is often more pronounced than the effect of herbivory. Our study highlights the importance of plant–soil feedbacks to determine the often‐unexplained intraspecific variation in chemical composition amongst plants.